Haiti : Staff Monitored Program. (IMF Staff Country Reports; Country Report ;, 2004)
This paper discusses the Staff-Monitored Program (SMP) for Haiti. The authorities have reached understandings with the IMF staff on a short-term SMP. The main objectives of the program are to preserve financial stability, support economic recovery, and establish a track record of policy implementation that could build a basis for a possible future request for the use of IMF resources. This program follows an earlier one-year SMP that was put in place in March 2003 and was expected to lead to a successor Poverty Reduction and Growth Facility arrangement in the second half of 2004.